Homotopy-perturbation method for heat transfer equations - Chowdhury, Md. Sazzad Hossien; Siddiquei, Hasin Reza; Rahman, M. M.; Ismail, A. F. (2010)

(untitled)
In this paper, we present a reliable new algorithm based on the homotopy-perturbation method (HPM) to determine the temperature distribution of a straight rectangular fin with power-law temperature dependent surface heat flux. The solution of the boundary-value problems (BVP) based on the homotopy-perturbation method (HPM) presented earlier is corrected and extended.